Synergistic Effects of Glutaric Acid With Sorbic Acid and Sodium Bisulphite on Preserving the Quality of Refrigerated Sliced and Minced Salmon - Zhengrui Liao (22501730) (2025)
The synergistic antimicrobial and antioxidant effects of glutaric acid (GLA) with sorbic acid (SoA) or sodium bisulphite (SoB) were evaluated to determine their optimal concentrations and ratios for maximum efficacy. The results revealed that these combinations exhibited strong antimicrobial properties, with GLA‐SoB also demonstrating significant antioxidant activity. These findings were consistent across both in vitro and food model (using salmon) evaluations. The combinations effectively extended shelf life and preserved freshness when applied to sliced and minced salmon. GLA, GLA‐SoA (2:1), and GLA‐SoB (1:2) were particularly effective in maintaining color, stabilizing pH and moisture levels, and reducing spoilage markers such as total volatile base nitrogen (TVB‐N), peroxide value (POV), thiobarbituric acid (TBA) levels, and microbial counts. This study highlights the comparable effectiveness of GLA‐SoB (1:2) and GLA‐SoA (2:1) in inhibiting microbial growth and extending the shelf life of salmon under refrigerated conditions. Both combinations showed dose‐dependent efficacy in preserving quality and safety, making them promising candidates for enhancing the storage stability of salmon products. Other Information Published in: Food Science & Nutrition License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/fsn3.70242